A super-hydrophilic electrolytic cell diaphragm material and preparation method thereof

By pretreating polyphenylene sulfide nonwoven fabrics, low-temperature plasma treatment, ultrasonic deposition of titanium dioxide precursors and high-temperature hydrolysis, nano-TiO2 super-hydrophilic shells are formed, the problem of poor hydrophilicity of existing alkaline electrolytic cell separators is solved, efficient electrolyte infiltration and ion transmission is achieved, energy consumption of hydrogen production in electrolytic water, and corrosion resistance and acid and alkali resistance of the separator are improved.

CN117051579BActive Publication Date: 2025-04-29ZHEJIANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310852606.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-04-29
Estimated Expiration
2043-07-12

AI Technical Summary

Technical Problem

The existing alkaline electrolytic cell separators have poor hydrophilicity, resulting in insufficient infiltration of the electrolyte and low ion transport efficiency, which increases the energy consumption of hydrogen production by electrolyzing water.

Method used

By pretreating the polyphenylene sulfide nonwoven fabric, low-temperature plasma treatment, ultrasonic deposition of titanium dioxide precursor and high-temperature hydrolysis, a nano-TiO2 superhydrophilic shell layer is formed, and the hydrophilicity and ion permeability of the separator are improved.

Benefits of technology

The ultra-hydrophilicity of the polyphenylene sulfide electrolytic cell separator is realized, the infiltration of the electrolyte and the rapid transmission of ions are improved, the energy consumption of hydrogen production by electrolyzing water is reduced, and the corrosion resistance and acid and alkali resistance of the separator are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117051579B_ABST
    Figure CN117051579B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a super-hydrophilic electrolytic cell diaphragm material, comprising: pre-treating a fiber material in an organic solvent; treating the pre-treated fiber material with a low-temperature plasma; soaking the fiber material treated with the low-temperature plasma in a TBT ethanol solution for ultrasonic treatment, and drying to obtain a fiber material deposited with a titanium dioxide precursor; soaking the fiber material deposited with the titanium dioxide precursor in heated deionized water for hydrolysis, washing and drying the hydrolyzed fiber material to obtain a super-hydrophilic electrolytic cell diaphragm material. The present invention also discloses an electrolytic cell diaphragm material prepared by the above-mentioned preparation method. The raw materials of the present invention are easy to obtain, the preparation process is simple, and it is easy to control. The prepared electrolytic cell diaphragm material has super-hydrophilicity, strong corrosion resistance and acid and alkali resistance, and good stability and ion permeability, and is suitable for large-scale promotion and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical industry, relates to a membrane hydrophilic modification technology, and specifically relates to a super-hydrophilic electrolytic cell membrane material and a preparation method thereof. Background Art

[0002] As an efficient, clean and ideal secondary energy source, hydrogen energy has always been widely valued around the world. The development of hydrogen energy has important strategic significance. Among the common hydrogen production technologies, water electrolysis is simple to operate and the technology is relatively mature. It is an important means to achieve large-scale hydrogen production.

[0003] The electrolytic cell diaphragm is a key part of the electrolytic water hydrogen production device. Its main function is to isolate the hydrogen and oxygen produced by the electrocatalytic water decomposition process and ensure the efficient and free movement of ions in the electrolyte. At the same time, the diaphragm also needs to have a certain chemical stability and physical stability to meet the requirements during assembly and operation.

[0004] For a long time, the main raw material of alkaline electrolytic cell diaphragms was asbestos. Although asbestos has advantages such as good hydrophilicity and free movement of ions, it has high resistance and high electrolysis energy consumption. At the same time, asbestos itself has poor swelling and chemical stability, short life, and carcinogenic toxicity, which limits the application of the material. Therefore, attempts have begun to use polymer materials as electrolytic cell diaphragms.

[0005] Polyphenylene sulfide (PPS) is a material with excellent acid and alkali resistance, corrosion resistance, radiation resistance, thermal stability and flame retardancy. It also has excellent creep resistance and good dimensional stability. The composite diaphragm is prepared with PPS non-woven fabric as the substrate. PPS as the substrate can provide a certain physical support. At the same time, the diaphragm has excellent heat resistance, excellent mechanical properties, high chemical stability and long life, but its hydrophilicity is poor. If only PPS non-woven fabric is used as a diaphragm, it is not conducive to the infiltration of electrolyte and the transmission of ions. There will be a large internal resistance at the diaphragm, resulting in high energy consumption for hydrogen production by electrolysis of water. Therefore, it is necessary to hydrophilically modify the PPS fiber membrane, enhance its hydrophilicity, improve its conductivity, ensure the infiltration of electrolyte and the rapid transmission of ions, solve the problem of gas expansion, and make the alkaline electrolyzer operate efficiently, safely, stably and for a long time.

[0006] The patent document with the announcement number CN111733602A discloses a method for preparing a PPS / MOFs micro-nano fiber alkaline water electrolyzer diaphragm, which includes preparing a PPS melt-blown cloth from a dry PPS resin through a melt-blown device; hydrophilic modification of the PPS melt-blown cloth; modification of the hydrophilic modified PPS melt-blown cloth with alkali-resistant hydrophilic MOFs; hot pressing the MOFs-modified PPS melt-blown cloth, and rapidly cooling it to obtain a PPS / MOFs micro-nano fiber alkaline water electrolyzer diaphragm. The invention uses the hydrophilic ZIF-90 modification method to improve the hydrophilicity and alkali absorption rate of the diaphragm.

[0007] Titanium dioxide (TiO2) is a semiconductor with particularly good hydrophilicity, photocatalytic ability, high chemical stability, corrosion resistance, low price, and environmental protection. The surface of TiO2 contains a large number of hydroxyl groups, which provide chemical bonds for it to combine with cellulose molecules and are widely used in the hydrophilic modification of polymer membranes.

[0008] At present, there are two main methods for hydrophilic modification of composite membranes, namely surface modification and blending modification. Surface modification is further divided into surface coating and surface grafting. The modification of surface coating method generally only occurs on the membrane surface, and the coating layer is easily damaged or even separated from the membrane surface, which can easily cause problems such as membrane pore blockage and decreased water flux.

[0009] Surface grafting is a chemical and physical method such as plasma treatment and UV irradiation, which utilizes the active sites on the membrane surface to graft and polymerize with hydrophilic groups to generate a hydrophilic composite layer to achieve the purpose of hydrophilic modified membrane. The active sites are connected to the modifier by covalent bonds, and the structure is stable. It is one of the more commonly used modification methods. However, plasma treatment is prone to unevenness and often only occurs on the membrane surface, resulting in little improvement in the water permeability of the membrane, affecting the working efficiency of the electrolytic cell diaphragm. Therefore, it is urgent to develop a new method to overcome the above-mentioned defects of the prior art to prepare a polyphenylene sulfide electrolytic cell diaphragm with super hydrophilic properties. Summary of the invention

[0010] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for preparing a super-hydrophilic electrolytic cell diaphragm material. The method obtains a super-hydrophilic electrolytic cell diaphragm by pretreating a fiber material, performing low-temperature plasma treatment, ultrasonic deposition and high-temperature hydrolysis. The method has a simple process, is easy to control, and is suitable for large-scale promotion and application.

[0011] A method for preparing a super-hydrophilic electrolytic cell diaphragm material comprises the following steps:

[0012] (1) Fiber material pretreatment: soaking the fiber material in an organic solvent, ultrasonic cleaning, and drying;

[0013] (2) low temperature plasma treatment: subjecting the fiber material obtained in step (1) to low temperature plasma treatment;

[0014] (3) Ultrasonic deposition: preparing a TBT ethanol solution, immersing the fiber material obtained in step (2) in the TBT ethanol solution for ultrasonic treatment, and drying to obtain a fiber material with a titanium dioxide precursor deposited thereon;

[0015] (4) High temperature hydrolysis: soaking the fiber material deposited with titanium dioxide precursor obtained in step (3) in heated deionized water for hydrolysis, washing and drying the hydrolyzed fiber material to obtain a super hydrophilic electrolytic cell diaphragm material.

[0016] Preferably, in step (1), the fiber material is polyphenylene sulfide fiber.

[0017] More preferably, the fiber material has a unit weight of 400 to 500 g / m 2 , a polyphenylene sulfide blended non-woven felt cloth (PPS) with a thickness of 1 to 2.5 mm, wherein the heat resistance of the polyphenylene sulfide blended non-woven felt cloth is 150° C. and above.

[0018] The present invention firstly performs ultrasonic cleaning on a PPS non-woven fabric to remove grease and dust on the surface of the non-woven fabric; then the surface of the PPS non-woven fabric is treated by low-temperature plasma technology, so that a large number of active sites are generated on the surface of the PPS non-woven fabric, polar groups such as hydroxyl groups on the surface of the PPS non-woven fabric are activated, and the adsorption performance of the surface of the PPS non-woven fabric is increased; then a titanium dioxide precursor is deposited on the surface and inside of the PPS non-woven fabric by ultrasonic dispersion, so that a uniformly distributed nano-TiO2 super-hydrophilic shell layer is formed on the surface and inside of the non-woven fabric; finally, super-hydrophilic modification of a hydrophobic film is achieved by high-temperature hydrolysis, and during the hydrolysis process, the surface of the titanium dioxide precursor nano-particles on the surface and inside of the PPS non-woven fabric is contacted with water to react and be gradually hydrolyzed to form nano-TiO2. Before hydrolysis, SO-Ti and CO-Ti bonds had been formed in the PPS fiber material during ultrasonic deposition of the titanium dioxide precursor and a small amount of TiO2 nanoparticles were generated; after hydrolysis, the titanium precursor was fully dehydrated to form TiO2 nanoparticles, which improved the crystallinity of the TiO2 shell, thereby obtaining a super hydrophilic electrolytic cell diaphragm material.

[0019] Preferably, in step (1), in addition to polyphenylene sulfide fiber, the fiber material may also be polytetrafluoroethylene fiber, polysulfone fiber, acrylic fiber, polyester fiber or filter paper. The main components of these fiber materials are all high molecular polymers with similar structures, containing a large number of polar groups such as hydroxyl, carboxyl, and amino groups. Due to the presence of these groups, there are certain reactive sites on the surface of these materials to react.

[0020] In step (1), the organic solvent is one or a mixed solvent of ethanol, acetone or isopropanol.

[0021] Preferably, the organic solvent is a mixed solvent of ethanol, acetone and isopropanol, and the volume ratio of ethanol, acetone and isopropanol in the mixed solvent is 1:1:1.

[0022] The present invention firstly pre-treats the PPS non-woven fabric, and then ultrasonically cleans the PPS non-woven fabric in a mixed solvent of ethanol, acetone and isopropanol to remove grease and dust on the surface of the non-woven fabric.

[0023] Preferably, in step (1), the ultrasonic cleaning power is 120 to 240 W, and the time is 15 min to 2 h.

[0024] Preferably, in step (2), the discharge voltage of the low-temperature plasma treatment is 60 to 80 V, the current is 1 to 1.8 A, and the time is 1 to 10 min.

[0025] Preferably, in step (2), the atmosphere of the low-temperature plasma treatment is one or more of air, oxygen and argon.

[0026] More preferably, the atmosphere of the low-temperature plasma treatment is a mixture of 30% oxygen and 70% argon.

[0027] The present invention uses low-temperature plasma technology to treat the surface of the PPS non-woven fabric, so that a large number of active sites are generated on the surface of the PPS non-woven fabric, polar groups such as hydroxyl groups on the surface of the PPS non-woven fabric are activated, and the adsorption performance of the membrane surface is increased; at the same time, the number of active sites generated on the surface of the PPS non-woven fabric and the number of hydrophilic polar groups such as hydroxyl groups introduced can be regulated by changing the plasma treatment atmosphere and the length of the treatment time.

[0028] Preferably, in step (3), the volume ratio of TBT to ethanol in the TBT ethanol solution is 1 to 3:20.

[0029] Preferably, in step (3), the temperature of the ultrasonic treatment is 5 to 35° C., the power is 120 to 240 W, and the time is 15 min to 2 h.

[0030] More preferably, the temperature of the ultrasonic treatment is 20-25° C., the power is 180-240 W, and the time is 30 min to 1 h.

[0031] The present invention soaks the PPS nonwoven fabric treated by low-temperature plasma technology in a TBT (tetrabutyl titanate) ethanol solution, and uniformly and fully deposits the titanium dioxide precursor on the surface and inside of the PPS nonwoven fabric through ultrasonic dispersion. Ultrasonic energy can effectively avoid the large-scale agglomeration problem that nanoparticles are very likely to produce, thereby forming a uniformly distributed nano-TiO2 super-hydrophilic layer on the surface and inside of the nonwoven fabric. In this process, SO-Ti and CO-Ti bonds are formed in the PPS nonwoven fabric and a small amount of TiO2 nanoparticles are generated. Ultrasonic treatment improves the hydrophilicity and stability of the fiber membrane, achieves excellent ion permeability of the diaphragm, and solves the problems of gas expansion membrane separation and the like.

[0032] In addition, the power and time of ultrasonic treatment have a great influence on the deposition of titanium precursor. When the ultrasonic treatment time is short, the shell of titanium dioxide precursor loaded on the surface of PPS non-woven fabric is thin and uneven; with the increase of ultrasonic treatment time, the shell of titanium dioxide precursor becomes thicker, and more tiny titanium precursor nanoparticles are attached to the shell; if the ultrasonic deposition is too long, the shell of titanium dioxide precursor is too thick and cracks will occur.

[0033] Preferably, in step (4), the temperature of the deionized water is 40 to 85° C., and the hydrolysis time is 2 to 24 hours.

[0034] More preferably, the temperature of the deionized water is 60-70° C., and the hydrolysis time is 6-18 hours.

[0035] Preferably, in step (4), the washing is performed by washing with ethanol and deionized water respectively. Washing can remove impurities on the surface of the hydrolyzed fiber material and excessively deposited TiO2 particles.

[0036] During the hydrolysis process, the surface of the titanium dioxide precursor nanoparticles came into contact with water and reacted to gradually hydrolyze to form nano-TiO2. Before hydrolysis, SO-Ti and CO-Ti bonds had already formed in the PPS non-woven fabric during ultrasonic deposition of the titanium dioxide precursor, and a small amount of TiO2 nanoparticles were generated; after hydrolysis, the titanium precursor was fully dehydrated to form TiO2 nanoparticles, which increased the crystallinity of the TiO2 shell and made the prepared electrolytic cell diaphragm material super-hydrophilic.

[0037] Preferably, in step (1), step (3) and step (4), the drying temperature is 75°C.

[0038] The present invention also provides a super-hydrophilic electrolytic cell diaphragm material prepared by the above preparation method. The electrolytic cell diaphragm material has super-hydrophilicity, strong corrosion resistance and acid and alkali resistance, and good stability and ion permeability, and is suitable for large-scale promotion and application.

[0039] Preferably, the contact angle of the super hydrophilic electrolytic cell diaphragm material is 0°.

[0040] Compared with the prior art, the present invention has at least the following beneficial effects:

[0041] (1) The present invention uses low-temperature plasma technology to treat PPS non-woven fabrics, so that active sites are generated on the surface of the PPS non-woven fabrics, thereby increasing the adsorption performance of the surface of the PPS non-woven fabrics; at the same time, the number of active sites generated on the surface of the polyphenylene sulfide fiber membrane and the number of hydrophilic polar groups such as hydroxyl groups introduced can be regulated by changing the plasma treatment atmosphere and the treatment time.

[0042] (2) The present invention deposits titanium dioxide precursor uniformly and fully on the surface and inside of the PPS non-woven fabric through ultrasonic treatment, effectively avoiding the problem of nanoparticle agglomeration, improving the hydrophilicity and stability of the PPS non-woven fabric, achieving excellent ion permeability of the diaphragm, and solving problems such as gas expansion membrane separation.

[0043] (3) The preparation method of the present invention makes the growth of TiO2 nanoshell on the surface and inside of the PPS non-woven fabric significantly affected by the ultrasonic time and the hydrolysis time. The desired size of titanium dioxide particles and their distribution inside the fiber membrane can be obtained by changing the ultrasonic time and the hydrolysis time, thereby achieving its superhydrophilic modification.

[0044] (4) After the polyphenylene sulfide super hydrophilic non-woven fabric prepared by the present invention is treated with strong acid and strong alkali, the hydrophilicity and water retention of the non-woven fabric are basically unchanged, indicating that the polyphenylene sulfide super hydrophilic non-woven fabric prepared by the present invention has strong corrosion resistance and acid and alkali resistance, and can be used in the work of alkaline electrolytic cells.

[0045] (5) The method of the present invention has a simple process, and the raw materials are easy to obtain and control, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the technical solution of the present invention, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0047] Figure 1 The scanning electron microscope photo and the corresponding EDS spectrum of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in Example 1 are shown, wherein (a) is a scanning electron microscope photo and (b) is an EDS spectrum.

[0048] Figure 2 This is a scanning electron microscope photograph of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in Example 2.

[0049] Figure 3This is the X-ray diffraction pattern of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in Example 2.

[0050] Figure 4 These are experimental photos of the rapid water absorption of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in Example 2, (a) is before water absorption, (b) is after water absorption, the blue droplets are methylene blue aqueous solution, and the transparent solvent is petroleum ether.

[0051] Figure 5 These are photos of the oil-water separation experiment of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in Example 2, (a) is before separation, (b) is after separation, the transparent upper solution is petroleum ether, and the blue lower solution is methylene blue solution.

[0052] Figure 6 This is a scanning electron microscope photograph of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in Example 3.

[0053] Figure 7 These are contact angle photos of the polyphenylene sulfide super hydrophilic nonwoven fabrics prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0054] Various exemplary embodiments of the present invention are now described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art in the art described in the present invention. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention.

[0055] Example 1

[0056] (1) Fiber material pretreatment

[0057] Cut the polyphenylene sulfide non-woven fabric into a size of 5 cm×5 cm, prepare a mixed solvent of ethanol, acetone, and isopropanol (20 ml:20 ml:20 ml) with a volume ratio of 1:1:1, soak the polyphenylene sulfide non-woven fabric in a beaker containing the organic solvent, take it out after ultrasonication for 30 minutes, and dry it at 75°C.

[0058] (2) Low temperature plasma treatment

[0059] Under the conditions of 75V discharge voltage, 1.5A current and 240W power, the dried polyphenylene sulfide non-woven fabric was treated with low-temperature air plasma. The discharge electrode was placed 5 cm above the non-woven fabric. After the discharge arc was stable, the plasma discharge electrode was moved continuously, both on the front and back sides for 5 minutes.

[0060] (3) Ultrasonic deposition

[0061] Prepare a TBT ethanol solution, soak the non-woven fabric in the TBT ethanol solution (TBT 5 mL, ethanol 40 mL) at 25° C., and perform ultrasonic treatment for 30 minutes. After the ultrasonic treatment, dry the obtained non-woven fabric at 75° C. to obtain a non-woven fabric with titanium dioxide precursor particles deposited thereon.

[0062] (4) High temperature hydrolysis

[0063] The non-woven fabric with deposited titanium dioxide precursor particles was immersed in deionized water at 70°C, taken out after 12 hours, washed with ethanol and deionized water respectively to remove surface impurities and excessively deposited TiO2 particles, and dried at 75°C to obtain a polyphenylene sulfide super hydrophilic non-woven fabric.

[0064] The scanning electron microscope photo of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in this example and the corresponding EDS spectrum are shown in FIG. Figure 1 (a) and Figure 1 (b) Figure 1 (a) It can be seen that the fiber surface is evenly and completely covered with a hydrophilic shell composed of TiO2 nanoparticles, indicating that TiO2 has been evenly deposited on the surface and inside of the PPS non-woven fabric, and is tightly combined with the polyphenylene sulfide fiber, effectively avoiding the problem of nanoparticle agglomeration. Figure 1 (b) It can be seen that both Ti and O elements can be detected on the fiber surface, which indicates that TiO2 nanoparticles are successfully prepared on the fiber surface.

[0065] Table 1 shows the oil-water separation efficiency data of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in this embodiment, wherein the oil solution is petroleum ether and the aqueous solution is methylene blue solution. As shown in Table 1, the oil-water separation efficiency of the polyphenylene sulfide super hydrophilic nonwoven fabric in this embodiment is as high as 98.4%.

[0066] Example 2

[0067] (1) Fiber material pretreatment

[0068] Cut the polyphenylene sulfide non-woven fabric into a size of 5 cm×5 cm, prepare a mixed solvent of ethanol, acetone, and isopropanol (20 ml:20 ml:20 ml) with a volume ratio of 1:1:1, soak the polyphenylene sulfide non-woven fabric in a beaker containing the organic solvent, take it out after ultrasonication for 30 minutes, and dry it at 75°C.

[0069] (2) Low-temperature plasma

[0070] Under the conditions of 75V discharge voltage, 1.5A current and 240W power, the dried polyphenylene sulfide non-woven fabric was plasma treated in a mixed gas atmosphere of 30% oxygen and 70% argon. The discharge electrode was placed 5 cm above the non-woven fabric. After the discharge arc and atmosphere flux were stable, the plasma discharge electrode was moved continuously, both on the front and back sides for 5 minutes.

[0071] (3) Ultrasonic deposition

[0072] Prepare a TBT ethanol solution, soak the non-woven fabric in the TBT ethanol solution (TBT 5 mL, ethanol 40 mL) at 25°C, and perform ultrasonic treatment for 30 minutes. After the ultrasonic treatment, dry the obtained non-woven fabric at 75°C to obtain a non-woven fabric with titanium dioxide precursor particles deposited thereon.

[0073] (4) High temperature hydrolysis

[0074] The non-woven fabric with deposited titanium dioxide precursor particles was immersed in deionized water at 70°C, taken out after 12 hours, washed with ethanol and deionized water respectively to remove surface impurities and excessively deposited TiO2 particles, and dried at 75°C to obtain a polyphenylene sulfide super hydrophilic non-woven fabric.

[0075] The scanning electron microscope photo of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in this example is shown in Figure 2 It can be observed that the fiber surface is evenly and completely covered with a hydrophilic shell composed of TiO2 nanoparticles, indicating that TiO2 has been evenly deposited on the surface and inside of the fiber membrane and is tightly combined with the polyphenylene sulfide fiber, effectively avoiding the problem of nanoparticle agglomeration. The X-ray diffraction pattern of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in this example is shown in Figure 3 , compared with the standard PDF card, it shows that this example successfully prepared anatase TiO2. The experimental photos of the rapid water absorption of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in this example are shown in Figure 4 , cut 2cm 2 The polyphenylene sulfide super hydrophilic nonwoven fabric sample was immersed in a beaker. When it came into contact with blue methylene blue water droplets, the water droplets were quickly absorbed, indicating the super water absorption of the sample. The oil-water separation experiment photo of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in this example is shown in Figure 5 The oil-water separation efficiency data are shown in Table 1. Figure 4 , Figure 5 As shown in Table 1, the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in this embodiment has an oil-water separation efficiency of up to 98.7% and rapid solution wettability.

[0076] Example 3

[0077] (1) Fiber material pretreatment

[0078] Cut the polyphenylene sulfide non-woven fabric into a size of 5 cm×5 cm, prepare a mixed solvent of ethanol, acetone, and isopropanol (20 ml:20 ml:20 ml) with a volume ratio of 1:1:1, soak the polyphenylene sulfide non-woven fabric in a beaker containing the organic solvent, take it out after ultrasonication for 30 minutes, and dry it at 75°C.

[0079] (2) Low-temperature plasma

[0080] Under the conditions of 75V discharge voltage, 1.5A current and 240W power, the dried polyphenylene sulfide non-woven fabric was treated with a mixed gas plasma of 30% oxygen and 70% argon. The discharge electrode was placed 5 cm above the non-woven fabric. After the discharge arc and atmosphere flux were stable, the plasma discharge electrode was moved continuously, both on the front and back sides for 5 minutes.

[0081] (3) Ultrasonic deposition

[0082] Prepare a TBT ethanol solution, soak the non-woven fabric in the TBT ethanol solution (TBT 5 mL, ethanol 40 mL) at 25°C, and perform ultrasonic treatment for 1.5 hours. After the ultrasonic treatment, dry the obtained non-woven fabric at 75°C to obtain a non-woven fabric with titanium dioxide precursor particles deposited thereon.

[0083] (4) High temperature hydrolysis

[0084] The non-woven fabric with deposited titanium dioxide precursor particles was immersed in deionized water at 70°C, taken out after 24 hours, washed with ethanol and deionized water respectively to remove surface impurities and excessively deposited TiO2 particles, and dried at 75°C to obtain a polyphenylene sulfide super hydrophilic non-woven fabric.

[0085] The scanning electron microscope photo of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in this embodiment is shown in Figure 6 The fiber surface is evenly and completely covered with a TiO2 hydrophilic shell layer, and tiny TiO2 nanoparticles are precipitated.

[0086] The changes in water absorption of the polyphenylene sulfide super-hydrophilic non-woven fabric prepared in this embodiment before and after immersion in strong acid and strong alkali solutions are shown in Table 2. First, cut 4 pieces of polyphenylene sulfide super-hydrophilic non-woven fabric samples prepared in this embodiment with a size of about 2 square centimeters and weigh the original mass; then soak the sample in an aqueous solution and measure the water content of the sample after sufficient water absorption (water content before treatment); take 1 piece as a control group, and soak the other 3 pieces in a NaOH solution with a pH of 13, a KOH solution with a pH of 13, and a HCl solution with a pH of 1 for 12 hours, take out and dry, and test the water content of the sample again after sufficient water absorption (water content after treatment). It can be seen from Table 2 that the polyphenylene sulfide super-hydrophilic non-woven fabric prepared in this embodiment can absorb about 3 times its own weight of water, and has strong water absorption. After strong acid and strong alkali treatment, the hydrophilicity and water retention of the non-woven fabric are basically unchanged, indicating that the polyphenylene sulfide super-hydrophilic non-woven fabric prepared by the present invention has strong corrosion resistance and acid and alkali resistance, and can be used in the work of alkaline electrolytic cells.

[0087] Table 3 shows the pH value changes of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in this embodiment after being soaked in acid and alkali solutions of different pH values. As shown in Table 3, after the polyphenylene sulfide super hydrophilic nonwoven fabric is soaked and filtered in acid and alkali solutions of different pH values, the pH value of the acid and alkali solutions is basically unchanged, and H + and OH - They move freely in the electrolytic cell, reflecting the excellent ion mobility of the diaphragm; at the same time, the pH value of the solution has no obvious effect on the ion mobility of the membrane during the experiment.

[0088] Comparative Example 1

[0089] (1) Fiber material pretreatment

[0090] Cut the polyphenylene sulfide non-woven fabric into a size of 5 cm×5 cm, prepare a mixed solvent of ethanol, acetone, and isopropanol (20 ml:20 ml:20 ml) with a volume ratio of 1:1:1, soak the polyphenylene sulfide non-woven fabric in a beaker containing the organic solvent, take it out after ultrasonication for 30 minutes, and dry it at 75°C.

[0091] The polyphenylene sulfide nonwoven fabric without further treatment after pre-cleaning was taken as comparative example 1. The contact angle photos of the polyphenylene sulfide super hydrophilic nonwoven fabrics prepared in comparative example 1 and example 1 are shown in Figure 7 ,Depend on Figure 7 It can be observed that the original polyphenylene sulfide nonwoven fabric is a hydrophobic film with a contact angle of 131.6°, and after modification it becomes superhydrophilic with a contact angle of 0°.

[0092] Table 1 Oil-water separation efficiency of polyphenylene sulfide super hydrophilic nonwoven fabrics prepared in Examples 1-3

[0093] sample Example 1 Example 2 Example 3 Separation efficiency 98.4% 98.7% 98.9%

[0094] Table 2 Changes in water absorption of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in Example 3 before and after immersion in strong acid and strong alkali solutions

[0095]

[0096] Table 3 pH values ​​of the polyphenylene sulfide super hydrophilic nonwoven fabric prepared in Example 3 after being immersed in acid and alkali solutions with different pH values

[0097] Solution type Deionized water NaOH KOH HCl pH of solution before osmosis 7.08 12.81 12.82 0.03 pH of solution after osmosis 7.09 12.78 12.82 0.03

Claims

1. A method for preparing a super-hydrophilic electrolytic cell diaphragm material, characterized in that: The following steps are involved: (1) Fiber material pretreatment: soaking the fiber material in an organic solvent, ultrasonic cleaning, and drying; the fiber material has a unit weight of 400-500 g / m 2 , a polyphenylene sulfide blended non-woven felt fabric with a thickness of 1 to 2.5 mm, wherein the heat resistance of the polyphenylene sulfide blended non-woven felt fabric is 150° C. or above; (2) Low-temperature plasma treatment: subjecting the fiber material obtained in step (1) to low-temperature plasma treatment; (3) Ultrasonic deposition: preparing a TBT ethanol solution, soaking the fiber material obtained in step (2) in the TBT ethanol solution for ultrasonic treatment, and drying to obtain a fiber material deposited with a titanium dioxide precursor; the ultrasonic treatment temperature is 5-35°C, the power is 120-240W, and the time is 15min-2h; (4) High temperature hydrolysis: The fiber material deposited with the titanium dioxide precursor obtained in step (3) is immersed in heated deionized water for hydrolysis, and the hydrolyzed fiber material is washed and dried to obtain a super hydrophilic electrolytic cell diaphragm material.

2. The preparation method according to claim 1, characterized in that: In step (2), the discharge voltage of the low-temperature plasma treatment is 60-80 V, the current is 1-1.8 A, and the time is 1-10 min.

3. The preparation method according to claim 1, characterized in that: In step (2), the atmosphere of the low-temperature plasma treatment is one or more of air, oxygen, and argon.

4. The preparation method according to claim 1, characterized in that: In step (3), the volume ratio of TBT to ethanol in the TBT ethanol solution is 1-3:

20.

5. The preparation method according to claim 1, characterized in that: In step (4), the temperature of the deionized water is 40-85° C., and the hydrolysis time is 2-24 h.

6. The super hydrophilic electrolytic cell diaphragm material prepared by the preparation method according to any one of claims 1-5.

7. The super hydrophilic electrolytic cell diaphragm material according to claim 6, characterized in that: The contact angle of the super-hydrophilic electrolytic cell diaphragm material is 0°.

Citation Information

Patent Citations

  • Preparation method of PPS / MOFs micro-nano fiber alkaline water electrolytic cell diaphragm

    CN111733602A

  • Preparation method of titanium dioxide modified wool fiber

    CN105506957A

  • Hydrophilic polytetrafluoroethylene microfiltration membrane and preparation method thereof

    CN107174981A